Planning educational visits for the early years - Salaman, Anna.; Tutchell, Suzy.; Sage eBooks (London : Paul Chapman, 2005)
This step-by-step guide will show you how to get the best out of visits in the early years, whether you are going to the zoo down to the farm, exploring the arts, visiting a museum or going to a show.
Specialized.
Description based on print version record.
Includes index.
Keywords: School field trips -- Planning; Education, Preschool -- Activity programs -- Planning; Electronic books